The complete plastid genome of Grateloupia filicina (Rhodophyta) and phylogenetic analysis - Jing Zhang; Xianming Tang; Wei Zhou Chen; Tao Liu; Yue Li (Mitochondrial DNA. Part B. Resources, 2018)
In this study, we obtained the complete plastid genome of Grateloupia filicina (Lamouroux) C. Agardh using the high-throughput sequencing method. It had circular mapping organization with the length of 195,990 bp and contained 265 genes including 195 protein-coding genes, three rRNA genes, one tmRNA gene, 28 tRNA genes and 38 unidentified open reading frames (ORFs). Moreover, phylogenetic analysis revealed that G. filicina firstly clustered with Grateloupia taiwanensis. The complete plastid genome obtained in this work would be useful for further understanding the evolution of Grateloupia.